Factors influencing purchasing decisions of house purchaser : a case study at BINARAYA PKINK Sdn. Bhd / Nurul Atikah Abd Latif - Abd Latif, Nurul Atikah (2012)
The aim of this study is to identify the Factors Influencing Purchasing Decisions of House Purchaser: A Case Study at Binaraya PKINK Sdn. Bhd. There are fourth factors that will be studied, which are price, design, family size and quality. This study also conducted to examine what is the most influence factor that influencing customers’ purchasing decision among the house purchaser at Binaraya PKINK Sdn. Bhd. Moreover, questionnaires have been used in order to get feedback from customers. Then, the researcher will analyze the data from questionnaires using Statistical Package for Social Science 16.0 Students Version. The data will interpret and test using frequency distribution analysis and mean. Other than that, hypotheses will be test using correlation analysis, correlation coefficient and multiple regressions. Researcher will distribute 100 questionnaires to select Binaraya PKINK Sdn. Bhd. customers who deal with this cooperation. The collecting data is then tested on its Frequency analysis. Next, analyze using Reliability analysis and Hypotheses analysis. The findings of this paper revealed that the most factor that influence purchasing decision among of house purchaser is quality factor. Based from the result obtained, researcher suggest some recommendations that can help Binaraya PKINK Sdn. Bhd to increase the standard of houses that it offered to customers and able to compete with others competitors in the current real estate market.